Analysis of Direct Private Investment: The Case of Bachelor’s Level in Community College - Paudel, Min Raj (Education and Development, 2019)
The costs spent by students or parents while attaining education are called the direct private costs which are usually placed outside and inside the domain of educational institutions. The present study is a quantitative survey that aims to conduct a comparative analysis of institutional and non-institutional direct private costs. Furthermore, it tries to find the size of institutional and non-institutional direct private costs at Bachelor’s level education in Nepal. For these purposes, I have selected a community based college from Kathmandu valley purposively and 90 students of Bachelor’s level (30 each from the faculty of humanities, education and management) were selected using simple random sampling technique. The findings of the study reveal that the average college related institutional unit cost per student was Rs. 24730.57, university related institutional cost was Rs. 5982.23; and total annual institutional unit cost was Rs. 30712.80. Likewise, it was found that a student has expensed Rs. 46411.63 as non-institutional direct private cost in a year. Total annual average direct private cost of education (institutional plus non-institutional) was Rs. 77124.43 at Bachelor’s level of community based college in the capital city of Nepal.